Thermodynamic analysis of the open system of thermal water desalation with air heating - Podstievaia, T.; Sereda, V. (Energy and Automation, 2023)
With the increase in the world population and industrialization, the use of water resources for industry and domestic needs is also increasing. At the same time, the impact of the water sector on climate change is increasing due to emissions of greenhouse gases associated with the energy processes of water production, transportation and purification. Given that efforts aimed at mitigating the consequences of climate change are not enough today, it is very important to develop new ambitious strategies for sustainable development and decarbonization.The purpose of the work is a mathematical study of the air humidification-dehumidification cycle to obtain fresh water and the search for optimal parameters that will ensure the maximum efficiency of the desalination process.The principle of operation was considered and a mathematical model of the thermal water desalination system with air heating at the entrance to the humidifier in the solar heater was developed. A comprehensive thermodynamic analysis of the proposed scheme was made. The temperatures of air and salt water at the outlet of the heat exchangers were determined. The main energy parameters of the system were calculated with the help of balance equations.Graphical dependences of energy indicators on the operating parameters of the installation were constructed and analyzed. The change in performance and energy efficiency as a function of temperature and air velocity at the inlet to the humidifier is shown. The effect of air and salt water consumption on the energy efficiency and geometric dimensions of the humidifier was revealed.A comparison of the efficiency of open water desalination schemes with heating of air and water at the entrance to the humidifier is given. It was established that, under the same conditions, water heating provides higher energy parameters than air heating. The expediency of simultaneous heating of water and air at the entrance to the humidifier to further increase the efficiency of thermal desalination using the air humidification-dehumidification cycle was noted.Key words: energy efficiency, air humidification-dehumidification, thermodynamic analysis, mathematical modeling, thermal desalination